Analytical Study on Role and Impact of Demonetization in Online Shopping: Exploring the Effects of Demonetization on the Online Shopping Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The move of 'Demonetization' by the Hon'ble Prime Minister of India, Mr. Narendra Modi influenced everyone on November 08, 2016. It came about into a frenzy circumstance since individuals were shy of money in their grasp. Demonetization affected web shopping at introductory stage yet later the online merchants saw complex increment in their deals and income. The results of this prompted the utilization of advanced installments and online exchanges in pretty much all aspects of the nation. This move likewise expanded the utilization of advanced and versatile wallets offered by different organizations and banks. It is otherwise called pulling back of a specific type of cash from dissemination.